Improving the quality of nurse clinical documentation for chronic patients at primary care clinics: A multifaceted intervention - Ozayr H. Mahomed; Salsohni Naidoo; Shaidah Asmall; Myra Taylor (AOSIS, 2015)
Background: Deficiencies in record keeping practices have been reported at primary care level in the public health sector in South Africa. These deficiencies have the potential to negatively impact patient health outcomes as the break in information may hinder continuity of care. This disruption in information management has particular relevance for patients with chronic diseases. Objectives: The aim of this study was to establish if the implementation of a structured clinical record (SCR) as an adjunct tool to the algorithmic guidelines for chronic disease management improved the quality of clinical records at primary care level. Method: A quasi-experimental study (before and after study with a comparison group) was conducted across 30 primary health care clinics (PHCs) located in three districts in South Africa. Twenty PHCs that received the intervention were selected as intervention clinics and 10 facilities were selected as comparison facilities. The lot quality assurance sampling (LQAS) method was used to determine the number of records required to be reviewed per diagnostic condition per facility. Results: There was a a statistically significant increase in the percentage of clinical records achieving compliance to the minimum criteria from the baseline to six months post-intervention for both HIV patients on antiretroviral treatment and patients with non-communicable diseases (hypertension and diabetes). Conclusions: A multifaceted intervention using a SCR to supplement the educational outreach component (PC 101 training) has demonstrated the potential for improving the quality of clinical records for patients with chronic diseases at primary care clinics in South Africa.